Community Consultations to Support Scoping Review Knowledge Dissemination - Sarah L. Canham; Rachel Weldrick; Elizabeth Siantz; Jeffrey N. Rose; Danielle Maude Littman; Morgan Cruz Erisman; Kyle Rehn; Shannon Jones; Sumiko Anderson; Anne McNamara; Emma Greenwood (International Journal of Qualitative Methods)
Scoping reviews are a valuable form of literature review used to synthesize many types of evidence found in academic literature. Amidst the recommended best practices for conducting scoping reviews, little attention has been given to how to conduct community consultations as part of scoping review processes. The objective of this article is to describe one form that community consultation can take. As the final step in a scoping review project examining the stigmatization and discrimination of persons experiencing homelessness, our research team conducted a community consultation, designed as a Knowledge Café workshop, with 25 participants who had lived experiences of homelessness (past and present) or were service providers in the homelessness sector. The 3-hour workshop was conducted in a central public library with participants seated at different roundtables. The workshop was divided into four discussion periods during which participants described experiences, outcomes, or interventions related to the stigmatization and discrimination of persons experiencing homelessness. At the end of the workshop, participants completed a brief survey about the quality of the workshop, aspects that worked well, and what could be improved. Participants reported appreciating that the workshop provided a forum for combining research findings with personal stories, as well as opportunities to make or revive professional connections. Participants also reported that tangible event outcomes, a more future-oriented focus on solutions, and a longer event would have improved their experience. Study findings contribute to the literature on how to engage with community around collaborative problem-solving and the importance of incorporating diverse perspectives, fostering empathy and inclusivity, and translating ideas into actionable steps.